(untitled) (Tribhuvan University Journal of Microbiology, 2019)
Objectives: This study was aimed to compare the antibacterial activity of peel and juice extracts of citrus fruits. Methods: The antibacterial activity of juice and peel extract of five selected citrus fruits [C1- Citrus reticulata (mandarin orange), C2- Citrus limetta (sweet lime), C3- Citrus aurantifolia (lime), C4- Citrus limon (lemon) and C5- Citrus maxima (pommelo)] on three Gram positive and five Gram negative bacterial strains were examined. The juice and peel extract of citrus fruits was obtained by using absolute ethanol. The obtained extracts were dissolved in 1ml 10% v/v DMSO which was taken to carry out the antibacterial susceptibility assay using agar well diffusion method. Results: The peel extracts of C1 and C2 were found to be more effective against the given Gram-positive bacteria than the juice extracts with maximum zone of inhibition (20.33±1.527) and (15.33±0.577) against Bacillus spp respectively. While the juice extracts of C3 and C4 were more effective against both Gram positive and negative bacteria than their peel extracts with maximum zone of inhibition (26.66±1.15) against S. aureus ATCC 25923 and (20±1) against E. coli ATCC 25922 respectively. The juice extract of C5 was found to be more effective against both Gram positive and negative bacteria than its peel extract with maximum zone of inhibition (18.66±1.154) against E. coli ATCC 25922 except for Bacillus spp in which peel extract showed maximum zone of inhibition i.e. (15±1) Conclusion: This study suggests that these juice and peel extracts may have beneficial antibacterial roles that can be exploited in controlling unwanted bacterial growth.